Dictyanthus stevensii (Apocynaceae; Asclepiadoideae; Gonolobinae), a new species from Chimalapas region, Oaxaca, Mexico - González-Martínez, César Adrián; Lozada-Pérez, Lucio; Alvarado-Cárdenas, Leonardo O. (Phytotaxa, 2019)
A new species of the genus Dictyanthus is herein described and illustrated, more than 30 years since the last paper describing new species of this genus. Dictyanthus stevensii sp. nov. is known only from the Zoque forest in the Chimalapas region in the state of Oaxaca, Mexico. This species differs from all other species because it has the smallest flowers within the genus. It is morphologically related to D. eximius, a microendemic species of Chiapas. Information on the distribution and habitat of this new species is given, and its conservation status is proposed as Critically Endangered B2ab(ii). An identification key to Dictyanthus species in southern and southerneast Mexico is also provided.